2012
DOI: 10.1530/rep-11-0483
|View full text |Cite
|
Sign up to set email alerts
|

FGF10 inhibits dominant follicle growth and estradiol secretion in vivo in cattle

Abstract: Fibroblast growth factors (FGFs) are involved in paracrine control of follicle development. It was previously demonstrated that FGF10 decreases estradiol (E 2 ) secretion in granulosa cell culture and that theca cell FGF10 mRNA expression is decreased in healthy follicles from abattoir ovaries. The main objectives of this study were to evaluate FGF10 and FGFR2b mRNA expression during follicular development in vivo, to evaluate the effect of FGF10 on follicle growth using Bos taurus taurus cows as a model, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 40 publications
1
28
1
1
Order By: Relevance
“…In present study, our data regarding FGF10 expression pattern is not in line of agreement with earlier finding in human (Taniguchi et al, 2008), goat (Chaves et al, 2010) and cattle follicle (Buratini et al, 2007;Gasperin et al, 2012) where FGF10 mRNA expression was found to be decreased in mature or healthy follicle of human, goat and bovine ovary. In another study in human preantal follicle (Oron et al, 2012) FGF10 mRNA was observed regularly which is in opposition with our present data in relation to FGF10 expression pattern in bubaline follicle.…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…In present study, our data regarding FGF10 expression pattern is not in line of agreement with earlier finding in human (Taniguchi et al, 2008), goat (Chaves et al, 2010) and cattle follicle (Buratini et al, 2007;Gasperin et al, 2012) where FGF10 mRNA expression was found to be decreased in mature or healthy follicle of human, goat and bovine ovary. In another study in human preantal follicle (Oron et al, 2012) FGF10 mRNA was observed regularly which is in opposition with our present data in relation to FGF10 expression pattern in bubaline follicle.…”
Section: Resultscontrasting
confidence: 51%
“…FGF10 transcript level was significantly decreased in theca cells of mature follicles in bovine (Buratini et al, 2007;Gasperin et al, 2012), goat (Chaves et al, 2010) and in theca and stromal cells of human ovary (Taniguchi et al, 2008). FGF10 mRNA was significantly more expressed in subordinate follicle than the dominat follicle in cattle ovary (Gasperin et al, 2012).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Five to nine days later, the progesterone devices are removed and follicular dynamics is followed by daily ultrasound examination until the growing follicles of the new follicular wave reach the target diameter to perform intrafollicular injection or ovariectomy. Follicles are monitored at least three times before intrafollicular treatment to confirm that only new growing follicles and no aged follicles are present in the ovaries (Gasperin et al, 2012). Despite less timeconsuming in comparison to estrus detection-based protocols, many cows are usually removed from the experiment because large follicles fail to regress after progesterone exposure.…”
Section: Induction Of a New Follicular Wave And Ovulationmentioning
confidence: 99%
“…The relative mRNA expression was calculated based on the amplification of the reference gene GAPDH according to PFAFFL et al (2001). The primers used for the amplification of CYP17A1 (sense: CCATCAGAGAAGTGCTCCGAAT and antisense: GCCAATGCTGGAGTCAATGA), CYP11A1 (sense: CTTGCACCTTTCTGGCTAGG and antisense: AAGGGGAAGAGGTAGGGTGA), HSD3B2 (sense: GCCCAACTCCTACAGGGAGAT and antisense: TTCAGAGCCCACCCATTAGCT) and STAR (sense: CCCAGCAGAAGGGTGTCATC and antisense: TGCGAGAGGACCTGGTTGAT) were based on previous studies (GASPERIN et al, 2012) and were synthetized by Invitrogen.…”
Section: Qrt-pcrmentioning
confidence: 99%